Implementasi Gerakan Pramuka Dalam Pembentukan Karakter Peserta Didik Pondok Pesantren Madrasah Tsanawiyah Sultan Hasanuddin - Taha, Muhammad; Siraj, Arifuddin; Naro, Wahyuddin (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2019)
This research is entitled Scout Movement in Forming Character Students of Islamic Boarding Schools in Tsanawiyah Sultan Hasanuddin. This study aims to describe how scouting activities take place at the Sultan Hasanuddin Islamic Boarding School of Madrasah Tsanawiyah. To obtain answers to these problems, the authors use three methods of data collection; Observations, interviews and documentation. In this study using descriptive qualitative analysis and data analysis techniques used are; Data reduction, data discovery and data verification. The samples in this study were students of the Sultan Hasanuddin Islamic Boarding School of Tsanawiyah Islamic Boarding School. The results showed that the implementation of scouting activities in the formation of the character of students went well and smoothly with the support of several parties involved in the Sultan Hasanuddin Madrasah Tsanawiyah Islamic Boarding School environment by covering various activities, namely: ceremonies, marching skills training, passwords, pioneering, camp, and natural roaming as a form of activity that is able to become a forum for fostering religious character formation, honesty, love for the homeland, peace, courtesy, tolerance, national spirit, discipline, leadership, togetherness, skill, solidarity, and responsibility. Keywords: Implementation, Scout Movement, Character Formation.